Electron interactions with the FEBID precursor WCl6. (15th May 2016) - Neustetter, Michael; da Silva, Filipe Ferreira; Denifl, Stephan
Abstract : Rationale: Secondary electrons with an energy distribution below 100 eV are formed when high‐energy particles interact with matter. In the focused electron beam induced deposition, high‐energy beams are used to decompose organometallic compounds on surfaces. We investigated the electron ionisation of WCl6 and dissociative electron attachment to WCl6 in the gas phase in order to better understand the decomposition mechanism driven by secondary electrons. Methods: A double‐focusing mass spectrometer coupled with a Nier‐type ion source was used to perform the present studies. The electron ionisation studies were performed with an electron energy of 70 eV and dissociative electron attachment studies in the energy range of ~0–14 eV. Results: Tungsten hexachloride rapidly oxidises, leading to the formation of a mixture of pure WCl6 and WCl4 O together with WCl2 O2 species. The fragmentation of the three chlorinated compounds is effective, although electron ionisation to WCl6 leads to W + in contrast with WCl2 O2 and WCl4 O leading to WO2 + and WO +, respectively, as lighter fragments. With regard to electron attachment, decomposition of the precursor molecules is observed; however, W – was not detected within the detection limit of the instrument. Conclusions: Electron ionisation and dissociative electron attachment (DEA) to WCl6, WCl4 O and WCl2 O2 lead to strong fragmentation. In electron ionisation, the fragmentation by loss of chlorine atoms was observed for both WCl6 and the oxidised species. Additionally, the loss of all chlorine ligands is observable for WCl6 as well as the oxidised species. The DEA results have shown dissociation by the scission of chlorine atoms as well as by the scission of an oxygen atom. The formation of chlorine and oxygen anions was observed, indicating the formation of a neutral counterpart containing the metal atom, free to be attacked by the next electron. Copyright © 2016 John Wiley & Sons, Ltd.